Partnership Between Universities in Japan and South Africa - Maki, T.; Mashau, T.S.; Wolhuter, C.C. (South African Journal of Higher Education, 2025)
Cross-border partnerships are increasingly important for higher education in the twenty-first century (Oleksiyenko & Yang 2015, Sanders & Wong 2021:214). While virtually all universities in the world, in their pursuit of internationalisation, strive to enter into partnerships with universities abroad, there is no synthesis of literature on the many case studies on such partnerships or the various models of international partnership to guide such activities. The purpose of this chapter is to fill this lacuna and to serve as a frame for the chapters and discussions in the rest of the volume. The chapter commences with a survey of the contextual background: the essential international dimension of universities, the enhanced imperative for internationalisation in the contemporary era in history, and how international partnerships between universities are put into service of this need. The research method is then explained, followed by the rationales for forging international partnerships between universities. Steps and decisions in forging such partnerships are then outlined. Subsequently, modes or models of partnerships are surveyed. In the final sections, the benefits and challenges of forging international partnerships are highlighted, and lessons learned are enumerated. From this, suggestions for the path forward, regarding such partnerships in general, and between Japanese and South African universities in particular, are made.